1981
DOI: 10.1128/iai.33.2.426-433.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human neutrophil granule extracts on macromolecular synthesis in Neisseria gonorrhoeae

Abstract: Neisseria gonorrhoeae were exponentially killed for 120 min (i.e., they were prevented from forming colonies on agar) by extracts of human neutrophil granules; however, macromolecular synthesis, indicated by incorporation of radiolabeled precursors in trichloroacetic acid-precipitable material, continued at or above zero time control values for 45 min. Protein, deoxyribonucleic acid, and ribonucleic acid synthesis appeared to decrease simultaneously after 45 min. Little or no lysis of gonococci occurred during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(25 reference statements)
2
13
0
Order By: Relevance
“…Ultimately, this would lead to bacterial death if the lesion remained unrepaired. Consistent with the work of Rest and co-workers (Rest, 1979;Buck and Rest, 1981;Rock and Rest, 1988) and our own studies (Casey et al, 1985;Shafer et ai, 1986a,b) (Shafer et at., 1982). Gonococcal susceptibility to purified lysosomal cat G, prepared from human PMNL granules and treated with di-isopropylfluorophosphate (Shafer et al.…”
Section: Discussionsupporting
confidence: 92%
“…Ultimately, this would lead to bacterial death if the lesion remained unrepaired. Consistent with the work of Rest and co-workers (Rest, 1979;Buck and Rest, 1981;Rock and Rest, 1988) and our own studies (Casey et al, 1985;Shafer et ai, 1986a,b) (Shafer et at., 1982). Gonococcal susceptibility to purified lysosomal cat G, prepared from human PMNL granules and treated with di-isopropylfluorophosphate (Shafer et al.…”
Section: Discussionsupporting
confidence: 92%
“…The nonoxidative antimicrobial potential of crude, unfractionated extract from PMN granules (2,3,7,11) and isolated cationic granule proteins (4,9,11,(14)(15)(16)(17)(18)(19) has been extensively studied. Although cationic proteins are considered to be largely responsible for the nonoxidative antimicrobial activity of granule contents, the question of whether their activity accurately represents the total nonoxidative antimicrobial potential of PMN granule contents has been raised (2, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Although cationic proteins are considered to be largely responsible for the nonoxidative antimicrobial activity of granule contents, the question of whether their activity accurately represents the total nonoxidative antimicrobial potential of PMN granule contents has been raised (2, 7). Buck and Rest (2) showed that crude granule extract from human PMNs reduced the viability of N. gonorrhoeae without affecting macromolecular synthesis. Other investigators isolated cationic proteins from human PMN granules, Odeberg and Olsson (14) demonstrating that a fraction which contained several 25,000-molecular-weight proteins inhibited macromolecular synthesis by Staphylococcus aureus and E. coli and Weiss et al (18) showing that a protein with a molecular weight of 58,000 to 60,000 had little effect on macromolecular synthesis by several gram-positive and gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations